Alphacoronaviruses from bats captured in European Russia in 2015 and 2021 are closely related to those of Northern Europe - Korneenko, Elena V.; Samoilov, Andrei E.; Chudinov, Ivan K.; Butenko, Ivan O.; Sonets, Ignat V.; Artyushin, Ilya V.; Yusefovich, Alexander P.; Kruskop, Sergei V.; Sinitsyn, Sergei O.; Klyuchnikova, Ekaterina O.; Gladkikh, Anna S.; Dedkov, Vladimir G.; et al. (Frontiers in Ecology and Evolution, 2024)
IntroductionBats are considered the natural reservoirs of several viruses including coronaviruses (CoVs), two genera of which, alpha- and betacoronaviruses, infect humans. Despite widespread screening of bat samples for novel viruses, information on the diversity of coronaviruses in bats inhabiting Russian territory remains scarce. Here, we analyzed the presence and diversity of alphacoronaviruses (Alpha-CoVs) in bats from European Russia.MethodsFourty three fecal samples from bats of 8 species: P. nathusii, P. kuhlii, M. brandtii, M. daubentonii, N. noctula, V. murinus, M. dasycneme, and P. auritus were taken to study.Results and discussionWe detected Alpha-CoV RdRp gene fragments in 30% (13/43) of samples examined in 75% (6/8) of species sampled. Phylogenetic analysis of RdRp showed that most of the identified Alpha-CoV sequences fall into clades within the Pedacovirus subgenus, with minor clusters of nyctacoviruses or myotacoviruses. We assert that closely related pedacoviruses have been circulating for a long time (from 2015 to 2021) in a large region from European Russia to Northern Europe. We propose that closely related pedacoviruses collected from common areas represent a separate species, which we name NE-Alpha coronavirus, with its host being bats of the genus Pipistrellus that inhabit a region from the European part of Russia to Northern Europe. Among the animals sampled, 4.6% (2/43) carried two Alpha-CoVs related to different subgenera (pedacovirus/myotacovirus or pedacovirus/nyctacovirus) simultaneously. We confirmed the presence of two different Alpha-CoV subgenera related to pedacovirus and nyctacovirus in P. kuhlii captured in 2021 and kept in captivity using whole genome sequencing of these viruses. The presence of two or more coronaviruses in one individual animal host is an essential prerequisite for recombination to occur. We also obtained two Alpha-CoV whole genomes from two specimens of P. nathusii captured in 2015. The genomic organization of BatCoV/MOW15-21 and BatCoV/MOW15-23 was similar to other Alpha-CoVs, but the assembled genomes contained a long insertion in the ORF1ab gene which has not been described in other Alpha-CoVs, except for a single sequence from P. nathusii captured in the Netherlands. We propose that the insertion encodes a previously undescribed domain of unknown function, probably related to the SEA domain superfamily.